2018
DOI: 10.1111/acel.12800
|View full text |Cite
|
Sign up to set email alerts
|

FOXO are required for intervertebral disk homeostasis during aging and their deficiency promotes disk degeneration

Abstract: Intervertebral disk (IVD) degeneration is a prevalent age‐associated musculoskeletal disorder and a major cause of chronic low back pain. Aging is the main risk factor for the disease, but the molecular mechanisms regulating IVD homeostasis during aging are unknown. The aim of this study was to investigate the function of FOXO, a family of transcription factors linked to aging and longevity, in IVD aging and age‐related degeneration. Conditional deletion of all FOXO isoforms (FOXO1, 3, and 4) in IVD using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 45 publications
(73 reference statements)
2
70
0
Order By: Relevance
“…In our effort to elucidate the molecular mechanisms supporting miR-221 action in IVD cells, we focused on the effect of antagomiR-221 treatment on FOXO3, a member of forkhead ‘O’ class transcription factors that have been recently defined as critical mediators of IVD integrity and function [ 16 , 17 ]. Computational analysis performed with three miRNA databases (miRanda, DIANA-microT v5.0 and miRTarBase) on the 3′ UTR sequence of FOXO3 identified possible binding sites for miR-221.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our effort to elucidate the molecular mechanisms supporting miR-221 action in IVD cells, we focused on the effect of antagomiR-221 treatment on FOXO3, a member of forkhead ‘O’ class transcription factors that have been recently defined as critical mediators of IVD integrity and function [ 16 , 17 ]. Computational analysis performed with three miRNA databases (miRanda, DIANA-microT v5.0 and miRTarBase) on the 3′ UTR sequence of FOXO3 identified possible binding sites for miR-221.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, antagomiR-221 treated cells restored higher levels of FOXO3 and TRPS1 attenuating the grade of severity based on a molecular point of view. The appearance of FOXO3 (a miR-221 validated target in other contexts) after antagomiR-221 treatment together with the demonstration that miR-221 directly targets FOXO3 also in IVD cells is an important evidence, since the expression of this crucial transcription factor significantly decreased in human degenerated discs [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the translation of mechanical loading signals activates TGFβ signaling, which promotes IVD homeostatic processes (Bian et al, 2017). Recent studies also show that Runx2 is required for postnatal IVD maintenance (Alvarez-Garcia et al, 2018;Liao et al, 2019). Here, we found that postnatal loss of PRMT5 in cartilaginous lineages of the spine resulted in alterations in the normal gene expression in IVD and vertebral growth plate, including reduced expression of Prg4 as well as increased expression of COLX, which are both markers of early-onset degenerative disc.…”
Section: Prmt5 Regulates Homeostasis Of the Cartilaginous Tissues In mentioning
confidence: 52%
“…During postnatal development, chondrocytes continue to regulate spine homeostasis by maintaining a dynamic balance between the synthesis and degradation of extracellular matrix components in the cartilaginous tissues of the spine. These processes are regulated in part by key transcriptional regulators, including SOX9 (Henry et al, 2012) and RUNX2 (Alvarez-Garcia et al, 2018;Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the FoxO signaling pathway (rno04068, p value � 4.735e − 02) and MAPK signaling pathway (rno04010, p value � 4.672e − 02) were also significantly enriched. Many studies have reported that the FoxO and MAPK signaling pathway can regulate apoptotic activity involved in pain or the nervous system [31][32][33]. erefore, we speculate that EA can reverse the aberrant apoptotic activity in DRG neurons in CIP rats through the MAPK or/and signaling pathway.…”
Section: Discussionmentioning
confidence: 70%